Spatial and Temporal Solar Potential Variation Analysis in Uganda Using Measured Data - Katongole, Daniel N; Nyeinga, Karidewa; Okello, Denis; Mukiibi, Daniel; Mubiru, James; Kisira, Yeeko (Tanzania Journal of Science, 2013)
The paper presents an analysis of spatial and temporal solar potential variations in Uganda. The solar radiation potential distribution was investigated based on measured data from 56 ground meteorological stations across Uganda from January 2015 to February 2022. The data were recorded after every 5-minute interval. The monthly average daily Global Horizontal Irradiance (GHI) was analysed using the spatial inverse distance weighting (IDW) interpolation technique in ArcGIS 10.7.1. The GHI distribution was found to have maxima at equinox and minimum between June and July. The average global horizontal irradiation is found to be 1680 KWh per year, with a daily variability below 10%. This is above the threshold for solar energy applications and with such low variability, large scale solar PV plants can be installed with minimum backup requirements. Northern Uganda receives the highest average daily global horizontal irradiation of 5.38 Whm–2 day–1, while Western Uganda receives 4.16 Whm–2 day–1, the lowest. The average AM/PM ratio depicted a value above 2 for all regions in Uganda and therefore, optimal solar energy exploitation for fixed systems favours eastern orientation. The central, eastern and northern Uganda which is 69.3% of the country has relief favourable for large scale solar PV power plants and CSP facilities. Keywords: GHI, IDW, Global solar radiation, Solar insolation, PV power plants, Uganda